MODEL KOLABORATIF DALAM PENANGGULANGAN RISIKO BANJIR DI KABUPATEN LAHAT - Austin, Trecy; Hakim, Arif Rahman; Sutinah; Rossa, Clara Amelya (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2025)
This study aims to elaborate on the collaborative governance model for flood risk management in Lahat Regency. Using a qualitative approach, data were collected through field observations, in-depth interviews, and documentation. The research adopts Ratner’s theoretical framework of collaboration, which consists of three key dimensions: (1) identifying obstacles and opportunities, (2) debating strategies for influence, and (3) planning collaborative actions. The results reveal that the collaborative model has been generally implemented well, with active involvement of various stakeholders, including local government, disaster management agencies, and community groups, in both decision-making processes and disaster response strategies. However, several obstacles were identified. First, difficulties in accessing and managing disaster-related data, particularly regarding flood events, have hindered effective planning. Second, challenges in implementing strategies at the field level often arise due to limited resources or lack of coordination. Third, some stakeholders fail to participate consistently in post-disaster evaluation meetings, reducing the effectiveness of collaborative planning. These findings suggest that although the foundation for collaborative governance exists, there is a critical need to enhance institutional coordination, improve stakeholder communication, and establish a regular and inclusive evaluation mechanism. Strengthening these aspects will contribute to a more resilient and integrated flood risk management system in Lahat Regency.